Investigation into the interfacial stiffness ratio of stationary contacts between rough surfaces using an equivalent thin layer. (November 2019) - Sun, Yunyun; Xiao, Huifang; Xu, Jinwu
Highlights: An analytical model is developed to evaluate the interfacial stiffness ratio theoretically considering the interface as an equivalent thin layer. Effective moduli of the thin layer are derived by a homogenization process of the deformed asperities over the whole rough surface. The interfacial stiffness ratio depends on surface topographies, interfacial separations, and material properties of contacting bodies. The interfacial stiffness ratios predicted by the proposed model are basically consistent with experimental results. Abstract: This work presents a semi-analytical model to evaluate the interfacial stiffness ratio of stationary contacts between rough surfaces. The rough contact interface is described as a homogenized thin layer with effective moduli, which are employed to characterize the ratio of the tangential to normal contact stiffness. In conjunction with the micro-contact analysis of the deformed asperity, effective moduli of the homogenized layer are determined by an ensemble average process of the moduli produced by deformed asperities made over the rough interface. Results show that the sought ratio is related to the surface topography, interfacial separation, and material properties of contacting bodies. Variations of the interfacial stiffness ratio with the applied load for different surface topographies are presented. The proposed model of the stiffness ratio is verified by comparing with the previous models and experimental results eventually.